A pilot study of the effects of running training on visuospatial memory in MS: A stronger functional embedding of the hippocampus in the default-mode network?. (October 2020) - Huiskamp, Marijn; Moumdjian, Lousin; van Asch, Paul; Popescu, Veronica; Schoonheim, Menno Michiel; Steenwijk, Martijn D; Vanzeir, Ellen; van Wijmeersch, Bart; Geurts, Jeroen JG; Feys, Peter; Hulst, Hanneke E
Background/objective: Endurance exercise can improve memory function in persons with multiple sclerosis (pwMS), but the effects on hippocampal functioning are currently unknown. We investigated the effects of a running intervention on memory and hippocampal functional connectivity in pwMS. Methods/results: Memory and resting-state functional magnetic resonance imaging (fMRI) data were collected in a running intervention ( n = 15) and waitlist group ( n = 14). Visuospatial memory improvement was correlated to increased connectivity between the hippocampus and the default-mode network (DMN) in the intervention group only. Conclusion: As a result of endurance exercise, improvements in visuospatial memory may be mediated by a stronger functional embedding of the hippocampus in the DMN.